Role of Biosynthesized Ag-NPs Using Aspergillus niger (MK503444.1) in Antimicrobial, Anti-Cancer and Anti-Angiogenic Activities - Pasha, Akbar; Kumbhakar, Divya Vishambhar; Sana, Siva Sankar; Ravinder, Doneti; Lakshmi, B. Vijaya; Kalangi, Suresh K.; Pawar, Smita C. (Frontiers in Pharmacology, 2022)
Owing to the medicinal values of biological derived biomolecules and utilizing them in synergy with nanoscience to offer more accurate therapeutic options to various diseases is an emerging field. One such study we present here with highlights of synthesis and efficacy of biogenic silver nanoparticles produced from the extract of Aspergillus niger MK503444.1 as an antimicrobial, anti-cancerous and anti-angiogenic agent. The synthesized Ag-NPs were characterized following UV–vis, FTIR, X-ray diffraction, SEM and TEM, and found to possess bactericidal activity against the selected pathogenic microbes. Further, in vitro assessment of anti-proliferative, anti-metastatic and apoptotic effect of these biogenic Ag-NPs on HeLa cells have revealed that, Ag-NPs are almost equally comparable in their anti-cancer effects which is accomplished by MTT assay, DAPI staining, scratch wound assay, Matrigel invasion assay and flow cytometric analysis. This Ag-NPs have shown trivial cytotoxicity at the IC50 concentration on healthy cells over cancer cells with nearly 7 folds difference, indicating it as a selective anti-cancerous agent when doxorubicin was taken as a positive control. Synthesized Biogenic Ag NPs also shown to be anti-angiogenic in nature, which was established by in-vivo chick chorioallantois membrane assay. Where overall, in vitro studies in current investigation revealed that biogenic Ag-NPs positively induced anti-metastatic and anti-proliferative effect on cervical cancer cells.